Suppression of chatter in high-speed milling machine using spindle speed variation method with microphone feedback PID controlller - Madan Varmma, Suparmaniam (2019)
High-speed milling process is the most common and versatile technology compared with conventional milling process for machining productivity of metal cutting industry. However, the productivity of machining is often limited by chatter at high signed in milling process. Chatter is a wavy mark on a product surface finish that occurs when self-excited vibration developed during the process, which results in low surface final part then degree measure of tool wear and less in amount the spindle lifetime. Main purpose of this study is to suppress chatter by spindle speed variation method at highspeed machinery and a better surface finish. Before chatter study proceeds, nonconventional machining applied with the high-speed machining method. This experiment investigates the effects of varying combination of depth of cut and feed rate to tool wear rate length using metallurgical microscope and surface roughness using portable surface roughness tester after end milling of aluminium and P20 steel. Then, in further experiment, PID controller was developed to give on-line feedback to the machine based on data fed by the microphone sensor. The data received from microphone sensor is analyzed in time and frequency domain. Furthermore, after machining, result also was compared with the surface roughness and surface topography of all cutting conditions. Results gathered from high-speed machining method applied on non-conventional milling shows feed rate significantly influences the surface roughness value while depth of cut does not as the surface roughness value keep increasing with the increase of feed rate and decreasing depth of cut. Whereas, tool wear rate almost remain unchanged indicates that material removal rate strongly contributes the wear rate. In further experiment, material’s surface roughness and surface topography improved until 86.7% in active experiments better than initial experiments after spindle speed variation has been implemented together with highspeed milling technique. This proves that chatter occurrence during machining can be suppressed using spindle speed variation method with microphone feedback PID controller. The researches contribute to high-speed milling usage industries with extra benefits of high productivity and can conserve time and money. Moreover, this method could enable providing high efficiency, accuracy, quality of final workpieces and eliminates semi-finishing process.